First fossil larvae of Berothidae (Neuroptera) from Baltic amber, with notes on the biology and termitophily of the family - Wedmann, Sonja; Makarkin, Vladimir N.; Weiterschan, Thomas; Hörnschemeyer, Thomas (Zootaxa, 2013)
Four fossil larvae of Berothidae (Neuroptera) from Baltic amber are described in detail, and the main characters of a fifth larva are discussed briefly. Two first instars very probably belong to the Berothinae; the subfamilial affinities of three other (probably full-grown) larvae are unclear. The latter are characterized by features not found so far in extant taxa of Berothidae: antennae and labial palps with six to seven segments; ecdysial cleavage lines consist of only frontal and coronal sutures (the lateral suture is absent); pronotal sclerites large and very close to each other along midline. However, these larvae belong with certainty to Berothidae as indicated by the structure of their mouthparts, and their general appearance. Morphological and biological data on the larvae of Berothidae are summarized and analyzed. It is presumed that termitophily might have evolved during the Cretaceous (or in the early Cenozoic), and only in Berothinae (or in subfamilies closely related to this group). The Baltic amber berothid assemblage apparently included both termitophilous and non-termitophilous larvae.